2015
DOI: 10.1111/pirs.12065
|View full text |Cite
|
Sign up to set email alerts
|

‘One for all and all for one’: Cluster, employment, and the global economic crisis. Evidence from the German mechanical engineering industry

Abstract: How regional clusters – and the firms constituting it – respond to major economic shocks has only recently become the centre of attention in regional research. Taking the concept of ‘adaptive resilience’ as a point of departure, and using a mixed methods approach (firm survey, multivariate analysis, expert interviews), this study explores the response of cluster and non‐cluster firms of the German mechanical engineering sector during the initial phase of the crisis (2008–2009). Findings show a significantly mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Wrobel (2015) observed that employment in cluster firms developed better than in non-cluster firms during the 2008 financial crisis. From interviews in cluster firms, he concludes that regional embeddedness in networks as well as a high level of solidarity between cluster firms positively moderated the effects of the crisis.…”
Section: Background and Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Wrobel (2015) observed that employment in cluster firms developed better than in non-cluster firms during the 2008 financial crisis. From interviews in cluster firms, he concludes that regional embeddedness in networks as well as a high level of solidarity between cluster firms positively moderated the effects of the crisis.…”
Section: Background and Motivationmentioning
confidence: 99%
“…Based on two comparative case studies in China, Gong et al (2022) showed that a local institutional innovationthe Industrial Chain Chief Modelhelped to increase regional resilience of firms in clusters by reconfiguring and reshaping production networks. Wrobel (2015) observed that employment in cluster firms developed better than in non-cluster firms during the 2008 financial crisis. From interviews in cluster firms, he concludes that regional embeddedness in networks as well as a high level of solidarity between cluster firms positively moderated the effects of the crisis.…”
mentioning
confidence: 99%
“…Clusters are recognized as organizational structures capable of providing superior competitiveness for companies and developing regions (Delgado et al. , 2014; Schmitz, 1999; Wrobel, 2015; Zaccarelli, 2000). This geographic agglomeration of companies and associated institutions in a particular field presents strong interorganizational cooperation relationships; however, they can also present opportunism, conflicts of interest, non-cooperation and actions based on individual interests (Hervas-Oliver and Albors-Garrigos, 2014; Pinkse et al.…”
Section: Introductionmentioning
confidence: 99%